2002
DOI: 10.1007/s00122-001-0777-0
|View full text |Cite
|
Sign up to set email alerts
|

RFLP-facilitated investigation of the quantitative resistance of rice to brown planthopper (Nilaparvata lugens)

Abstract: Quantitative trait loci (QTLs), conferring quantitative resistance to rice brown planthopper (BPH), were investigated using 160 F(11) recombinant inbred lines (RILs) from the Lemont/Teqing cross, a complete RFLP map, and replicated phenotyping of seedbox inoculation. The paternal indica parent, Teqing, was more-resistant to BPH than the maternal japonica parent, Lemont. The RILs showed transgressive segregation for resistance to BPH. Seven main-effect QTLs and many epistatic QTL pairs were identified and mappe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
2

Year Published

2005
2005
2010
2010

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(30 citation statements)
references
References 15 publications
1
27
0
2
Order By: Relevance
“…Huang et al (2001) conducted QTL analysis of resistance genes derived from wild species (O. officinalis) and reported two QTLs, Qbp1 and Qbp2 on chromosomes 3 and 4, respectively. Xu et al (2002) reported seven main-effect QTLs and many epistatic QTLs associated with quantitative resistance to BPH using a recombinant inbred line derived from Teqing × Lemont populations. Su et al (2002) detected QTLs on chromosomes 2, 10, and 12 using a Nipponbare × Kasalath backcross population.…”
Section: Qtls Associated With Bph Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…Huang et al (2001) conducted QTL analysis of resistance genes derived from wild species (O. officinalis) and reported two QTLs, Qbp1 and Qbp2 on chromosomes 3 and 4, respectively. Xu et al (2002) reported seven main-effect QTLs and many epistatic QTLs associated with quantitative resistance to BPH using a recombinant inbred line derived from Teqing × Lemont populations. Su et al (2002) detected QTLs on chromosomes 2, 10, and 12 using a Nipponbare × Kasalath backcross population.…”
Section: Qtls Associated With Bph Resistancementioning
confidence: 99%
“…For example, the Bph11 (bph11), Bph12 (bph12) and Bph13 [Bph13(t)] genes are existing as duplicate genes. A new BPH resistance derived from IR1154-243 was located on chromosome 4 and was named as Bph11 (Xu et al 2002). However, the bph11 gene was identified in an introgression line derived from O. officianalis on chromosome 3 (Hirabayashi and Ogawa 1995).…”
Section: Bph Resistance Gene Clusters and Genes Of Ambiguitymentioning
confidence: 99%
“…Therefore, comparative analyses of genomic locations for disease resistance in rice chromosome 6 with creeping bentgrass LG 7 was also conducted. A QTL for BPHRS (brown planthopper resistance) is located 5 cM away from RZ516 (Xu et al 2002), and a blast resistance QTL is located close to RG213 (Talukder et al 2005), 30 cM away from RZ516. However, QTL for BBRS (bacterial blight disease resistance) and SHBTRS (sheath blight disease resistance) have not been reported on chromosome 6.…”
Section: Qtl Analysismentioning
confidence: 99%
“…It is of interest that plant resistance genes, including major (qualitative) and minor (quantitative, QTL) genes, tend to be clustered in the particular regions of chromosomes (Beavis et al 1991;Wang et al 1994;Xu et al 2002;Ramalingam et al 2003;Yang et al 2003). Aside from the bph19(t) gene, one major gene Bph13(t) and two QTLs were mapped on the short arm of rice chromosome 3 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…One QTL accounted for only 3.8% of the phenotypic variance was identified to a marker interval, RG944-RG348, which is farther than the Bph13(t) locus from the bph19(t) locus ( Fig. 2a; Xu et al 2002). Another QTL predominantly associated with a single resistance mechanism, antixenosis, was also identified to a marker interval, RG191-RZ678, which covers the bph19(t) location ( Fig.…”
Section: Discussionmentioning
confidence: 99%